2016
DOI: 10.1016/j.epsl.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Titanium-hydroxyl defect-controlled rheology of the Earth's upper mantle

Abstract: Experiments were conducted with hydrous olivine to investigate the defect responsible for the influence of water (hydrogen structurally incorporated as hydroxyl) on the olivine rheology. Solution-gelation derived Fo 90 olivine doped with nominally 0.04-0.1 wt.% TiO 2 was first hot-pressed and then deformed in platinum capsules at 300 MPa confining pressure and temperatures from 1200-1350 C. The water content was not bu↵ered so that deformation occurred at water-undersaturated conditions. Due to the enhanced gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 68 publications
(152 reference statements)
2
36
0
1
Order By: Relevance
“…Experimental studies have shown clear evidence for coupled substitution of hydrogen with these species in simple systems Berry et al 2007a;Faul et al 2016;Férot and Bolfan-Casanova 2012;Grant et al 2007a, b;Kovacs et al 2010), supported by atomistic simulations (Balan et al 2011;Blanchard et al 2017;Walker et al 2007). Furthermore, the FTIR spectra produced by these studies reproduce well the dominant absorbance bands of natural olivine crystals Schmädicke et al 2013;Tollan et al 2015).…”
Section: +mentioning
confidence: 99%
“…Experimental studies have shown clear evidence for coupled substitution of hydrogen with these species in simple systems Berry et al 2007a;Faul et al 2016;Férot and Bolfan-Casanova 2012;Grant et al 2007a, b;Kovacs et al 2010), supported by atomistic simulations (Balan et al 2011;Blanchard et al 2017;Walker et al 2007). Furthermore, the FTIR spectra produced by these studies reproduce well the dominant absorbance bands of natural olivine crystals Schmädicke et al 2013;Tollan et al 2015).…”
Section: +mentioning
confidence: 99%
“…Natural dunites deformed in the climb‐controlled dislocation creep regime were significantly weaker under hydrous conditions than under anhydrous conditions [ Carter and Ave'Lallemant , ; Chopra and Paterson , ]. Fine‐grained olivine aggregates deformed in both the climb‐controlled dislocation creep and diffusion creep regimes exhibit significant hydrolytic weakening [ Karato et al , ; Mei and Kohlstedt , , ; Demouchy et al , ; Tasaka et al , ; Faul et al , ]. Olivine aggregates deforming by glide‐controlled dislocation creep [ Katayama and Karato , ] also reveal hydrolytic weakening.…”
Section: Introductionmentioning
confidence: 99%
“…High oxygen fugacity has been shown to enhance seismic attenuation in olivine (Cline et al 2018). The similarly high oxygen fugacities present in the earlier deformation experiments of Faul et al (2016), produced by the platinum sleeve used to wrap the specimen (Faul et al 2017 In this study we use computational simulations to investigate the possibility that cation vacancies may be able to lubricate dislocation glide in forsterite by reducing the Peierls stress  p ., providing a mechanism by which point defects may influence the rheology of this important mantle mineral in the glide-controlled creep regime. Core structures and Peierls stresses are calculated for important slip systems in forsterite using a semi-discrete Peierls-Nabarro (PN;Peierls 1940;Nabarro 1947) model.…”
Section: Introductionmentioning
confidence: 99%
“…Martin and Donnay 1972;Bai and Kohlstedt 1993;Kohlstedt et al 1996;Lemaire et al 2004), can influence the rheology of olivine under conditions of low-temperature (<1273 K) and high-stress, reducing  p to 1.6-2.9 GPa (Katayama and Karato 2008). Similarly, the incorporation of water as the "titanoclinohumite" defect, consisting of charge-coupled {Ti M }˙˙ and {2H Si }″ defects apparently results in a systematic increase in strain rate (Berry et al 2005;Faul et al 2016). Protonated cation vacancies also change the preferred slip system in olivine.…”
Section: Introductionmentioning
confidence: 99%